2016
DOI: 10.3390/w8120579
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Managed Aquifer Recharge through Modeling—A Review

Abstract: Managed aquifer recharge (MAR) is the purposeful recharge of an aquifer for later recovery or environmental benefits and represents a valuable method for sustainable water resources management. Models can be helpful tools for the assessment of MAR systems. This review encompasses a survey and an analysis of case studies which apply flow and transport models to evaluate MAR. The observed modeling objectives include the planning or optimization of MAR schemes as well as the identification and quantification of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 105 publications
0
50
0
Order By: Relevance
“…Laboratory experiments allow one to focus on specific MAR aspects under well controlled conditions, e.g., to study the factors that affect the extent of removal of emerging compounds such as pharmaceuticals [31], or to assess the conditions that affect the risk of colloid-facilitated contaminant transport [32,33] or industrially produced nano-particles in the infiltrated source water. In addition, numerical modeling allows the assessment of water quantity and quality aspects for a wide range of MAR conditions, which can support the feasibility, design and optimization of MAR application [34].…”
Section: Effective and Reliable Mar Operationmentioning
confidence: 99%
“…Laboratory experiments allow one to focus on specific MAR aspects under well controlled conditions, e.g., to study the factors that affect the extent of removal of emerging compounds such as pharmaceuticals [31], or to assess the conditions that affect the risk of colloid-facilitated contaminant transport [32,33] or industrially produced nano-particles in the infiltrated source water. In addition, numerical modeling allows the assessment of water quantity and quality aspects for a wide range of MAR conditions, which can support the feasibility, design and optimization of MAR application [34].…”
Section: Effective and Reliable Mar Operationmentioning
confidence: 99%
“…The second section is located between AS and OB, with a length of 3.2 km, and its bedrock consists of alluvium and colluvium. The watershed area up to PB is 77 km 2 , up to AS 98 km 2 , and up to OB 105 km 2 . The study transect can be divided into two zones (Figure 1): the transient zone and the check dam zone.…”
Section: Transient Zonementioning
confidence: 99%
“…The sustainability of groundwater bodies is therefore very important, and induced groundwater recharge is one of the main methods for increasing the sustainable yield of a groundwater body [1][2][3]. Especially under climate change conditions, managed aquifer recharge systems could be more effective than increasing surface reservoir capacities [4] and could also be the most economically and socially feasible solution for the integrated management of water resources [5].…”
Section: Introductionmentioning
confidence: 99%
“…Common MAR methods include the direct injection of groundwater into an aquifer with well, shaft, or borehole recharge, water spreading methods such as flooding, induced infiltration of water into a streambank, storm or rainwater harvesting, and in-channel modifications that direct water to unsaturated aquifer infiltration zones or river sediments. An assessment of 226 case studies which apply water flow and transport models to evaluate different MAR methods found that spreading methods are the most commonly used MAR techniques worldwide [37]. According to the same assessment, modeling is typically performed during the planning phase of MAR execution to evaluate the feasibility of MAR at a suggested site.…”
Section: Natural Infrastructure and The Quantification Of Natural Watmentioning
confidence: 99%